FORMULATION, ORGANOLEPTIC TESTS AND ANTIOXIDANT ACTIVITIES CANDY OF JAMICU FROM GINGER (ZINGIBER OFFICINAL), MIANA (COLEUS ATROPURPUREUS L. BENTH.) AND CALAMANSI (CITROFORTUNELLA MICROCARPA) - Pratiwi Ishak (International Interdisciplinary Conference on Sustainable Development Goals, 2019)
Ginger (Zingiber officinal), miana (Coleus atropurpureus benth) and calamansi (Citrofortunella microcarpa) are plants that have high antioxidant activity. This activity is due to the content of flavonoids, anthocyanins, essential oils and minerals. However, it is unfortunate in Gorontalo that these three ingredients are only used as spices. Based on the content and lack of utilization of these three plants, reseacher to make a formula that is popular with the community, namely ginger-based jelly candy, miana and Calamansi which are rich in antioxidants and can increase endurance. The research method is true experiment. Organoletic test results show that Formula B is the most preferred formula. Microscopic tests and heavy metal tests show that Jamicu jelly candy fulfills the requirements of SNI 3547-02-2008 concerning Jelly Soft Confectionery. Antioxidant activity test results using the DPPH method show that Jamicu jelly candy has a very strong antioxidant activity (IC50 3.39 ppm)